Solar-diurnal geomagnetic field variations: seasonal and long-term changes of SqY, SqZ at the observatory AIA - O. Maksimenko; O. Shenderovskaya (Ukrainian Antarctic Journal, 2017)
The spatial ambiguity of the magnitude of centennial trends in the Sq variations diurnal amplitudes determined the investigation of this question in the region of negative century variations geomagnetic field. Objective. To study the characteristics (trends of diurnal amplitudes and shapes) of solar-diurnal Sq variations at the Antarctic observatory AIA. Methods. Analysis of geomagnetic field monitoring data at the observatory for the period 1958-1991. Exclusion of the effect of the dependence ofthe daily amplitude of Sq variations on the solar activity index F10.7 using the regression analysis residual method. Results. From the analysis of the shape of Sq variations, seasonal features of SqZ, SqY were obtained: autumn-spring asymmetry and an additional morning extremum in the daily course of Sq winter (April-September) type. Seasonal differences were found both in the mean monthly values of the daily amplitude of Sq variations and in the values of their long-term trend for 33 years. Conclusions. The revealed positive trends of the average annual daily amplitudes of Sq variations were 11% for the eastern SqY and 17-20% for the vertical SqZ variation. The observed variation in the trend value of the annual amplitudes Sq is apparently due to seasonal variations of the physical parameters that determine Sq.